The Effect of Tempra Finger Painting Technique on Color Mixing to Improve Cognitive Ability in Group A Hang Tuah Kindergarten, Bengkulu City - Inayah, Sheren; Nirwana, Evi Selva; Andani, Fidhia (Peneliti.net, 2025)
In Early Childhood Education (ECE) is a crucial stage in children’s cognitive development, serving as the foundation for future learning. Children aged 4–6 years are in a critical period of growth in recognizing concepts, including understanding and mixing colors. However, learning activities at this stage often encounter obstacles due to the lack of creative and engaging teaching methods. One alternative approach is the use of the finge painting technique with tempra paints. This study aims to examine the effect of the tempra finger painting technique on enhancing children’s cognitive abilities, particularly in color mixing. The research employed an experimental method with observational design involving Group A children at TK Hang Tuah Bengkulu City. Data were collected through direct observation of children’s learning activities and their artworks before and after the treatment. The findings revealed significant improvement in children’s cognitive abilities, including recognizing primary colors, mixing them into new combinations, and producing simple artworks according to instructions. The finge painting activity proved to be an effective stimulus that increased learning interest, developed logical thinking, creativity, and problem-solving skills in early childhood. Therefore, the tempra finger painting technique is recommended as an innovative teaching method in early childhood education. This research also suggests that teachers and parents should utilize more interactive and enjoyable learning media to optimize children’s cognitive development from an early age.